Role of PTEN gene in genetic alterations in endometrioid carcinoma - Fadhillah, Risti Sifa' (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2025)
Endometrioid (type I endometrial) carcinoma is the most prevalent form of endometrial cancer and is strongly associated with genetic alterations, particularly involving phosphatase and tensin homolog (PTEN) gene. PTEN protein is a crucial component of the protein kinase B (PKB)/Akt signaling pathway, which plays a significant role in regulating cell cycle arrest and inducing apoptosis. The loss or mutation of PTEN can disrupt this pathway, contributing to uncontrolled cell proliferation and cancer progression. Recent studies indicate that PTEN genetic alterations are not limited to mutations or loss of expression but also involve complex variations such as gene deletions, structural changes, and diverse regulatory disruptions. Genetic alterations involving PTEN are frequently observed in endometrioid-type endometrial carcinomas, particularly in tumors that develop from premalignant lesions. These alterations, whether mutations, deletions, or reduced expression, significantly disrupt the regulation of cell growth and key signaling pathways, thereby driving tumor initiation and progression. By providing a more integrated understanding of the multifaceted genetic changes in PTEN, this review highlights emerging opportunities for early detection, refined risk stratification, and the advancement of gene-targeted therapeutic strategies specifically for the endometrioid subtype of endometrial cancer.